3-D Printed Millimeter-Wave and Terahertz Lenses with Fixed and Frequency Scanned Beam - Yi, Huan; Qu, Shi-Wei; Ng, Kung-Bo; Chan, Chi Hou; Bai, Xue (IEEE transactions on antennas and propagation, 2016)
High-gain and beam-scanning antennas are extremely important in the applications of millimeter-wave (MMW) and terahertz (THz) technologies. Dielectric lens is a suitable candidate for this purpose, because it has no metal and quite small feeding loss. In this paper, discrete dielectric lenses are studied in which periodic antireflection (AR) structures are added to reduce impedance mismatch at the air-dielectric interfaces, leading to higher directivity. Meanwhile, a multifrequency phase matching method is proposed to realize a beam-scanning lens in both MMW and THz regions. The design concept of the beam-scanning lens is applicable to other frequency ranges as well, which opens new opportunities for future lens design. Moreover, three-dimensional (3-D) printing technology is employed to simplify the manufacturing process and reduce the cost. Experiments are done in both MMW and THz regions, and the results verify the concept of lens design. The 3-D printed MMW and THz lenses with fixed and scanning beams demonstrated in this work could be an important step toward MMW and THz communications, radar, and imaging systems for practical applications.